2013
DOI: 10.31989/ffhd.v3i6.52
|View full text |Cite
|
Sign up to set email alerts
|

Dietary omega-3 fatty acids and locomotor activity in an animal model of attention deficit hyperactivity disorder (ADHD)

Abstract: ABSTRACT:Background: Attention deficit hyperactivity disorder (ADHD) is the most frequent behavioral disorder of childhood and is characterized by hyperactivity, attention problems and impulsivity. Pharmacological and behavioral therapies have been shown to be effective. In addition, the role of dietary compounds in the etiology and possibly the treatment of ADHD has attracted increasing attention. For example, the lack of dietary essential fatty acids has been suggested to be associated with symptoms of ADHD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Motor coordination involves body movements comprising kinematic (such as spatial direction) and kinetic (force) parameters that result in the execution of an action/skill. Our study demonstrated that hyperlipidaemia dampens coordination skills, while administration of EPA þ DHA and zerumbone prevented hyperlipidaemiainduced dampening of motor coordination (29,30) . The poor performance of the HF group can be correlated to alterations in the normal functioning of the hippocampus, cortex, cerebellum and hypothalamus as they are mainly involved in the balanced regulation between the central and peripheral nervous system.…”
Section: Discussionmentioning
confidence: 52%
“…Motor coordination involves body movements comprising kinematic (such as spatial direction) and kinetic (force) parameters that result in the execution of an action/skill. Our study demonstrated that hyperlipidaemia dampens coordination skills, while administration of EPA þ DHA and zerumbone prevented hyperlipidaemiainduced dampening of motor coordination (29,30) . The poor performance of the HF group can be correlated to alterations in the normal functioning of the hippocampus, cortex, cerebellum and hypothalamus as they are mainly involved in the balanced regulation between the central and peripheral nervous system.…”
Section: Discussionmentioning
confidence: 52%